Ethanol sensing properties of PVP electrospun membranes studied by quartz crystal microbalance. (January 2016) - Aria, Mohammad Mohammadi; Irajizad, Azam; Astaraei, Fatemeh Razi; Shariatpanahi, Seyed Peyman; Sarvari, Reza
Abstract: In this study, ethanol gas sensing of PVP fiber membranes based on Quartz Crystal Microbalance (QCM) was investigated. The fibers were deposited on the QCM's electrodes by electrospinning the viscous blend solutions of PVP. The effects of PVP concentration on morphology of the fibers and their permeability when exposed to ethanol were investigated. Membranes which were prepared using low concentration solutions, contained beads and high packing fibers and showed low permeability. Increase of the PVP concentration to 12 wt% resulted in continuous fine fibers with good permeability. Furthermore, higher PVP concentrations were found to decrease ethanol permeability due to larger fiber radius and lower surface area. Moreover, effects of fibrous layer thickness on gas response was examined. Consequently, optimum amount of PVP concentration and fibrous layer thickness for the best gas response was found.